EVALUAREA IMPACTULUI TRATAMENTELOR ECOLOGICE DE PROTECȚIE A PLANTELOR ASUPRA PRODUCTIVITĂȚII FRUCTELOR DE TOMATE - Rotaru, Vlad (CEP USM, 2023)
Organic agriculture is gaining importance and the market for organic products has been increasing significantly nowadays. A greenhouse experiment was carried out to evaluate the influence of treatmnets with the biorational protection product Carbecol and humic substances Ecolit on fruits productivity of tomato plants. Tomato plants during vegetation period were treated four times with Carbecol in dose 6 kg/ha alone as well as in combination with application of biofertilizer Ecolit in doze 3 l/ha. Experimental results revealed that the application of Carbecol alone or in combination with treatmnets of Ecolit increased the yield of tomato. Therefore, the integrated application had a better effect and the yield increased by 15,7% compared to untreated plants.
ROTARU, Vlad. Evaluarea impactului tratamentelor ecologice de protecție a plantelor asupra productivității fructelor de tomate. In: Plant Protection - Achievements and Perspectives: scientific international symposium, Chisinau, October 2-3, 2023. CEP USM, 2023. pp.484-489. ISBN 978-9975-62-563-0. DOI:https://doi.org/10.53040/ppap2023.72.
Keywords: Solanum lycopersicum L.; Carbecol; Ecolit; Funecol; productivity